Severe Malnutrition With Gross Motor Developmental Delay In A 21-Month-Old Girl: A Family Medicine Case Report - Salsabila Rahma Fadlillah; Zita Atzmardina (Universitas Pahlawan Tuanku Tambusai, 2026)
Severe wasting is also referred to as severe acute malnutrition (SAM). It represents one of the most acute and life-threatening forms of malnutrition affecting vulnerable children worldwide with 13.6 million children under five globally. Indonesia's wasting prevalence (10.2%) exceeds Southeast Asia's 8.9% average, with severe wasting at 5.3%. Survivors face profound developmental delays, with neurobiological changes including reduced synapses and delayed myelination that persist despite nutritional recovery. We managed the toddler with SAM and gross developmental delay comprehensively, utilizing a family medicine approach. We made four home visits every week from July to August 2025 in the Cikupa Community Health Centre area. Patients are given a thorough and all-encompassing management plan, such as patient-centered interventions that involve a family and community approach. After weekly home visits for one month, the patient's weight and height increased. Although the patient's development remained at a score of 6, significant gross motor development was gradually occurring. This case exemplifies family medicine's transformative power in managing SAM with developmental delay through comprehensive management.